La mosquée en Algérie.Figures nouvelles et pratiques reconstituées - Abderrahmane Moussaoui (Université de Provence, 2009)
The “globalization” of religious discourse blurs the boundaries between the historically different schools, and tends to reduce the foundational gap between Sunnism and Shi’ism. Today we are experiencing a renewal of Salafism which recognizes only the fundamentals. Everything else is regarded as historical - therefore not sacred - and should be ignored or changed. The Salafi movement however continues to be divided between jâmida and jihâdiya. Practices within the mosque also vary as each individual seeks to demonstrate his individuality while following more global trends. The life stories of different imams reveal a sort of internal secularization of the mosque and greater flexibility in the re-interpretation of the fundamentals. Changes are also visible among new players who compete with the traditional Imam figure. The preacher figure, though not entirely new, nor a recent invention, remains a re-invented figure. While imams, muftis, and talebs are familiar in the Maghreb, the Da`Iya figure brought in by religious television channels is not as well known. Our study analyzes such changes taking place at the heart of the most important institution in Islam.